Assessing well-being among university students: A cross-cultural study in Hungary using optimal living profile-modified - Abu Khadra, Farah; Debes, Wessam A.; Takruri, Lina; Csapek, Zoltán; Kertai, Bendegúz; Jeges, Sára; Tóth, Ákos Levente (Journal of International Students, 2025)
In this paper, we aimed to define well-being challenges and how they relate to life satisfaction. A total of 112 Jordanian and 178 Hungarian students participated in the survey. Parametric, nonparametric statistical tests and confirmatory factor analysis were conducted to determine the optimal living profile. Group differences were analyzed to identify life satisfaction predictors. The findings revealed that Jordanians scored higher across all well-being dimensions, specifically in intellectual (mean 4.05 vs. 3.02) and emotional health (mean 3.95 vs. 3.00), with greater social support and optimism. Emotional and social health strongly predicted life satisfaction by 83.4%. This suggests that cultural background significantly impacts well-being and highlights the importance of university support for all students.